Technopreneurship in the digital business ERA of silk industry SMEs in Wajo Regency: The role of ecosystem and collaboration - Remmang, Hasanuddin; Suriani, Seri; Saleh, Haeruddin; Nur, Indrayani; Abubakar, Herminawati (International Journal of Management and Sustainability, 2025)
This study aims to analyze the determining factors for SME technopreneurship success in the Wajo Regency silk industry. The research approach used is a combination of qualitative and quantitative research. Data were obtained through observation, in-depth interviews, surveys, and documentation. The results of the study indicate that product innovation, technology adoption, human resource capabilities, financial support, network strength, and local government policies determine the success of SME technopreneurship. The silk industry in Wajo Regency has great potential to improve the regional economy but faces challenges adapting to the digital business era. The role of ecosystems and collaboration in technopreneurship in the digital business era directly impacts the acceleration of digitalization, which increases business efficiency, market access both nationally and internationally, and operational efficiency by reducing production and distribution costs. Technopreneurship, a form of technology-based entrepreneurship plays an important role in supporting the growth of SMEs in the digital business era. Utilization of digital platforms, partnership networks, and appropriate policy support can increase production efficiency, market access, and product innovation. Strengthening the digital capacity of SMEs, facilitating business incubation, and developing sustainable collaboration models in the technopreneurship ecosystem of the silk industry in Wajo Regency.